2011
DOI: 10.4161/cib.4.2.14257
|View full text |Cite
|
Sign up to set email alerts
|

Yeast dynamin implicated in endocytic scission and the disassembly of endocytic components

Abstract: The yeast dynamin-related GTPase Vps1 has been implicated in a range of cellular functions including vacuolar protein sorting, protein trafficking, organization of peroxisome and endocytosis.1,2 Vps1 is present at endocytic sites and may be directly involved in endocytic vesicle invagination through its membrane-tubulating activity. Here, evidence supporting the functional link between Vps1 and the yeast amphiphysin Rvs167 in vesicle invagination is discussed. Though the disassembly of endocytic factors from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Вторая стадия занимает примерно полминуты, в течение которых происходит сборка F-актина вокруг формирующейся везикулы. Далее происходит отшнуровывание эндоцитозной везикулы с помощью ГТФазы динамина либо, в случае бездинаминовых вариантов, с помощью белков амфифизинов [9]. У почкующихся дрожжей охарактеризован также клатриннезависимый путь поглощения FM4-64 [10].…”
unclassified
“…Вторая стадия занимает примерно полминуты, в течение которых происходит сборка F-актина вокруг формирующейся везикулы. Далее происходит отшнуровывание эндоцитозной везикулы с помощью ГТФазы динамина либо, в случае бездинаминовых вариантов, с помощью белков амфифизинов [9]. У почкующихся дрожжей охарактеризован также клатриннезависимый путь поглощения FM4-64 [10].…”
unclassified
“…In mammalian cells, in addition to Rvs161/167 homologues, the GTPase dynamin (Vps1 human homolog) is essential for scission of clathrin-coated vesicles. In yeast, the role of Vps1 in yeast endocytosis has been controversial [84], but recent reports demonstrated that Vps1 functions with the Rvs161/167 heterodimer to facilitate scission and release of the vesicles [61][62][63]85]. Indeed, Vps1 and Rvs167…”
Section: Discussionmentioning
confidence: 99%
“…Two of the five identified proteins, Rvs161 and Rvs167, function together in the vesicle scission step of the clathrin-mediated endocytosis pathway. Multiple studies have identified Vps1 as a third player in this mechanism [61,62]. Moreover, Vps1 and Rvs167 have been reported to function together during endocytosis [63].…”
Section: Ykr001c (Vps1)mentioning
confidence: 99%